Actuarial Aspects in Health Insurance - Muhammad Risalah Harahap; Nur Ahmadi Bi Rahmani (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2022)
Insurance is a guarantee or coverage against uncertain events (Sembiring, 1986). There are several types of insurance, namely health insurance, personal accident insurance, education insurance, and others. The type of insurance used in this study is health insurance. Everyone has a risk of developing a disease. If a person is stricken with a disease and is required to receive treatment and treatment in a hospital, it certainly requires a large amount of money and currently hospital costs are increasing. Therefore, preparation is needed to transfer these risks to insurance companies by participating in a health insurance program. This type of research is descriptive with a qualitative approach. Data collection used by using interviews, study documentation and observation. The study in this research is to find out